Tradeoffs in Crop Residue Utilization in Mixed Crop-Livestock Systems and Implications for Conservation Agriculture and Sustainable Land Management - Jaleta, Moti; Kassie, Menale; Shiferaw, Bekele (2012)
Crop residue use for soil mulch and animal feed are the two major competing purposes and the basic source of fundamental challenge in conservation agriculture (CA) where residue retention on farm plots is one of the three CA principles. Using survey data from Kenya and applying bivariate ordered Probit and bivariate Tobit models, this paper analyzes the tradeoffs in maize residue use as soil mulch and livestock feed in mixed farming systems. Results show that both the proportion and quantity of maize residue used for soil mulch and livestock feed are strongly affected by agroecology and livestock holding. Farmer knowledge about alternative use of crop residues and farmer perception of soil erosion risk (proxied through plot steepness) positively affect the amount of residue farmers retain on maize plots. Results imply that crop residue use as soil mulch in conservation agriculture is challenged in mixed croplivestock systems and particularly by smallholder farmers owning cross-bred and exotic dairy animals. In general, reducing the demand for crop residues as livestock feed through the introduction of alternative feed sources, better extension services on the use of crop residue as soil mulch and designing agroecology specific strategies and interventions could facilitate the adoption and expansion of CA-based practices in mixed crop-livestock systems.